Effect of Rhodiola Extracts on Learning, Memory Deficits and Micro Structure of Brain Cells Induced by Sleep Deprivation (Journal of Fatima Jinnah Medical University, 2018)
Objective：To Study the effect of Acanthopanax senticosus extract on the brain cell ultrastructure of rats model of sleep deprivation and its learning and memory deficits.Material and Methods: Brain cells ultrastructure were observed by transmission electron microscopy, rat model of sleep deprivation were made by using a modified multiple platform water environmental law, learning and memory ability were assessed by a maze test in rats.Results: In rat model of sleep deprivation group (SD group) there was obvious brain cell injury, learning and memory deficits and increased reaction time as compared to cage control group ( group CC) and tank control group ( group TC) ( p
Keywords: sleep deprivation; Rhodiola; brain cells; micro structure